Leaf Spectral Reflectance of Maize Seedlings and Its Relationship to Cold Tolerance. Issue 6 (27th September 2018) - Obeidat, Wisam; Avila, Luis; Earl, Hugh; Lukens, Lewis
Abstract : Increasing early‐season cold tolerance of maize ( Zea mays L.) has the potential to lengthen its growing season, reduce its environmental impact, and enhance its yields. Cold‐ and warm‐grown plants differ for biomass accumulation and spectral reflectance, the latter caused by differences in leaf chlorophyll content, carotenoid content, or other chemical and morphological attributes. Here, we evaluate genetic leaf spectral reflectance diversity across 38 inbred and 14 hybrid maize genotypes grown in cold and control temperatures. Genotypes varied for spectral reflectance indices correlated with chlorophyll content and for an index correlated with the ratio of leaf carotenoids to chlorophylls. Genotypic differences greatly contributed to spectral reflectance variation across all visible wavelengths, with the greatest genetic variation between 500 and 600 nm and around 700 nm. Cold treatment effects were most significant across the same wavelengths. Spectral indices indicated lower chlorophyll and a higher carotenoid/chlorophyll level in cold‐exposed plants relative to control plants. Genotype × temperature interactions were small relative to genotype effects. Cold tolerance, measured as the ratio of dry matter accumulation in cold‐treated plants relative to control plants, varied among hybrids and inbreds. Correlations of cold tolerance with known spectral reflectance indices, reflectance first derivatives, and novel, normalized spectral indices were mostly low and occurred only in certain germplasm. One reflectance parameter, the reflectance curve slope at 828 nm, was consistently related to genotypic cold tolerance, even when measured on plants that had not been exposed to cold.